2016
DOI: 10.1089/scd.2016.0165
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Mesenchymal Stem Cells in Sheep: Characterization and Autologous Transplantation in a Model of Articular Cartilage Repair

Abstract: Publisher Rights Statement:This is the final peer-reviewed manuscript as accepted for publication General rightsCopyright for the publications made accessible via the Edinburgh Research Explorer is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. Take down policyThe University of Edinburgh has made every reasonable effort to ensure that Edinburgh Research Explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
4
9
0
Order By: Relevance
“…More definite proof of a perivascular origin of MSCs was provided by seminal studies showing that pericytes in different human tissues stained for classical MSC markers and, on in vitro expansion, displayed an MSC phenotype while maintaining the expression of pericyte markers (CD146, PDGFRβ, NG2, αSMA). These findings have more recently extended to horse, dog and sheep , overall indicating that pericytes are in vivo counterparts of culture‐expanded MSCs in different species . Some of the previous studies also identified a population of adventitial cells (marked by the expression of CD34) as a perivascular cell type (in addition to pericytes) with MSC properties, and proposed these adventitial cells to be precursors of pericyte .…”
Section: A Perivascular Source Of Mscsmentioning
confidence: 71%
See 3 more Smart Citations
“…More definite proof of a perivascular origin of MSCs was provided by seminal studies showing that pericytes in different human tissues stained for classical MSC markers and, on in vitro expansion, displayed an MSC phenotype while maintaining the expression of pericyte markers (CD146, PDGFRβ, NG2, αSMA). These findings have more recently extended to horse, dog and sheep , overall indicating that pericytes are in vivo counterparts of culture‐expanded MSCs in different species . Some of the previous studies also identified a population of adventitial cells (marked by the expression of CD34) as a perivascular cell type (in addition to pericytes) with MSC properties, and proposed these adventitial cells to be precursors of pericyte .…”
Section: A Perivascular Source Of Mscsmentioning
confidence: 71%
“…Given the promising results obtained using human pericytes in animal models of tissue regeneration, significant interest has also arisen in the isolation and characterization of pericytes from veterinary species, either for the purpose of developing improved regenerative therapies for companion animals or use in preclinical models of human regenerative medicine. Isolation and culture of pericytes from species other than human and rodents has been particularly challenging due to the lack of specific antibodies, and only very recently were the first successful attempts reported (in sheep, horse, and dog) (Table ).…”
Section: Pericytes In Veterinary Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…The immunophenotype CD146+CD34-CD31-CD45-CD56- successfully isolates pericytes in multiple tissues including the skeletal muscle, bone marrow, white adipose tissue, placenta, pancreas, umbilical cord, heart, kidneys, infrapatellar fat pad, and liver [6, 9, 14, 18, 29, 30, 3538, 3941]. Of note, the same immunophenotype has been used to isolate pericytes from other mammalian species, including dog [42], sheep [43], and horse [44, 45], offering large animal models of perivascular cell-mediated tissue regeneration.…”
Section: Identification and Purification Of Perivascular Cells For Bomentioning
confidence: 99%